Comparation between Fibroscan and Hepatus for Detecting NAFLD in Patients with Metabolic Dysregulation - Sun, Jie-hui; Zhang, Ping-ping; Wang, Kun; Xu, Miao; Sun, Jing; Li, Li (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background The clinical application of the innovative instantaneous elasticity and fat attenuation measurement technology, Hepatus, is currently in the evaluation stage. This study aimed to compare the detection performance of Fibroscan and Hepatus in patients with metabolic dysregulation who are "at-risk" for non-alcoholic fatty liver disease (NAFLD).Methods Between January 2021 and April 2021, 149 patients were enrolled in this study. Clinical data were collected, and all patients underwent both Fibroscan and Hepatus assessments to determine liver stiffness measurement (LSM) and attenuation parameters. The correlation between the results obtained from the two transient elastography (TE) devices was analyzed. Receiver operating characteristic curves (ROC) were constructed to compare the diagnostic value of Fibroscan and Hepatus for Hepatic Steatosis Index (HSI)-based NAFLD.Results The detection success rate of Hepatus (100.0%) was higher than that of Fibroscan (96.0%). LSM (r = 0.663, P0.05) and attenuation parameters (r = 0.778, P0.05) obtained by Fibroscan and Hepatus were significantly correlated. Hepatus tended to produce a higher LSM (Hepatus vs. Fibroscan: 6.04 vs. 5.66 kPa, P=0.016) but a lower attenuation parameter than Fibroscan (Hepatus vs. Fibroscan: 264 vs. 277 dB/m, P0.001). The area under the ROC curve for detecting HSI-based NAFLD was 0.811 for Fibroscan and 0.832 for Hepatus.Conclusion Measurements obtained by Fibroscan and Hepatus are strongly correlated, and the diagnostic value of the two TE devices is comparable in detecting HSI-based NAFLD. Hepatus offer a potential TE alternative in NAFLD examination.